Preclinical evaluation of a novel silver gelling fiber dressing on Pseudomonas aeruginosa in a porcine wound infection model. Issue 4 (16th April 2019) - Davis, Stephen C.; Li, Jie; Gil, Joel; Head, Cheyanne; Valdes, Jose; Glinos, George D.; Solis, Michael; Higa, Alexander; Pastar, Irena
Abstract: The wound environment is a fertile ground for biofilm forming pathogens. Once biofilms form within the wound, they can be very challenging to eradicate. The purpose of this study was to examine the effect of a gelling fiber dressing with silver using a well‐established porcine wound biofilm model. Deep partial thickness wounds were inoculated with Pseudomonas aeruginosa ATCC 27312 and covered with a polyurethane film dressing to promote biofilm formation. Wounds were then divided into treatment groups: gelling fiber dressing with silver, gelling fiber dressing without silver, hydrofiber dressing with silver, benzethonium chloride and ethylenediaminetetraacetic acid and compared to untreated control. Microbiological, biofilm, and histological wound assessments were performed on days 3, 5, and 7 postinfection. Treatment with gelling fiber dressing with silver resulted in significant reduction of P. aeruginosa biofilm when compared to all other treatment groups on every assessment time point. In addition, gelling fiber dressing with silver treatment resulted in detachment of biofilm from the wound, while wounds treated with gelling fiber dressing with and without silver showed more granulation tissue formation on day 3. Our data show that a new gelling fiber dressing with silver was effective in reducing biofilm associated P. aeruginosa in vivo. This study may have important clinical implications especially for wounds heavily colonized with gram‐negative biofilm‐forming bacteria.